Robotic Surgery in Otolaryngology-Head and Neck Surgery: Yesterday, Today and Tomorrow - Bayram, Ali; Eskiizmir, Görkem; Cingi, Cemal; Hanna, Ehab (ENT Updates, 2020)
In the present review, we aim to give an overview of the development and utilization of robotic surgery in otolaryngology-head and neck surgery from its introduction, current status, and future applications. Robotic surgery has been applied either pre-clinically or is already in clinical use for several indications in otolaryngology and head and neck surgery. Due to its rapid progress and technological development, it appears it will be a more active tool in the future for the diagnosis and treatment of a number of diseases in otolaryngology-head and neck surgery practice.